2014
DOI: 10.1103/physrevlett.113.125301
|View full text |Cite
|
Sign up to set email alerts
|

Phase Imprinting in Equilibrating Fermi Gases: The Transience of Vortex Rings and Other Defects

Abstract: We present numerical simulations of phase imprinting experiments in ultracold trapped Fermi gases which are in good agreement with recent, independent experimental results. Our focus is on the sequence and evolution of defects using the fermionic time-dependent Ginzburg-Landau equation, which contains dissipation necessary for equilibration. In contrast to other simulations we introduce small, experimentally unavoidable symmetry breaking, particularly that associated with thermal fluctuations and with the phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 36 publications
8
36
0
Order By: Relevance
“…Indeed, there has been significant controversy and debate over the characterization and decay processes of various defects, notably those associated with a phase imprint in which ∆Φ ∼ π. There the original defect was thought to be a heavy soliton [5], later a vortex ring [7], and still later, as was consistent with predictions from some of our co-authors [8], established to be a solitonic vortex [6]. Similarly, defects formed via the Kibble-Zurek mechanism, using a temperature quench across the BoseEinstein condensation (BEC) transition, were originally mis-identified as solitons [9] and later determined to be solitonic vortices [10].…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…Indeed, there has been significant controversy and debate over the characterization and decay processes of various defects, notably those associated with a phase imprint in which ∆Φ ∼ π. There the original defect was thought to be a heavy soliton [5], later a vortex ring [7], and still later, as was consistent with predictions from some of our co-authors [8], established to be a solitonic vortex [6]. Similarly, defects formed via the Kibble-Zurek mechanism, using a temperature quench across the BoseEinstein condensation (BEC) transition, were originally mis-identified as solitons [9] and later determined to be solitonic vortices [10].…”
Section: Introductionsupporting
confidence: 52%
“…These studies address only the condensate dynamics and do not include the effects of fermionic excitations. Considerable support for these numerics comes from previous related studies [8] of phase imprinting near ∆Φ = π where most aspects of the experiments [6] confirmed the earlier predictions. In such simulations it is important to avoid artificially symmetric situations which unphysically stabilize long-lived defects.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations